2015
DOI: 10.3390/nano5021124
|View full text |Cite
|
Sign up to set email alerts
|

A Sustainable Approach to Fabricating Ag Nanoparticles/PVA Hybrid Nanofiber and Its Catalytic Activity

Abstract: Ag nanoparticles were synthesized by using Ficus altissima Blume leaf extract as a reducing agent at room temperature. The resulting Ag nanoparticles/PVA mixture was employed to create Ag nanoparticles/PVA (polyvinyl alcohol) hybrid nanofibers via an electrospinning technique. The obtained nanofibers were confirmed by means of UV-Vis spectroscopy, The X-ray diffraction (XRD), Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), and then tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(63 citation statements)
references
References 22 publications
8
40
0
Order By: Relevance
“…To further confirm the formation of AgNPs and ZnONPs X-ray diffraction patterns of the two samples were collected and are shown in The XRD results clearly show that the AgNPs and ZnONPs prepared by the Neem extract are both crystalline in nature. The crystallite size of AgNPs and ZnONPs were calculated by the Debye-Scherer's equation [47]:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To further confirm the formation of AgNPs and ZnONPs X-ray diffraction patterns of the two samples were collected and are shown in The XRD results clearly show that the AgNPs and ZnONPs prepared by the Neem extract are both crystalline in nature. The crystallite size of AgNPs and ZnONPs were calculated by the Debye-Scherer's equation [47]:…”
Section: Resultsmentioning
confidence: 99%
“…Many plant products such as Azadirachta indica (Neem) leaf extract [38,44,45]. Tribulus longipetalus extract [40], Acacia nilotica pods [46], Ficus altissima Blume leaf extract [47], and aqueous leaf extracts of Emblica officinalis [42], are capable of reducing metal ions to nanoparticles because of their antioxidant properties. Furthermore, plant extracts produce capping agents for the stabilization of nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…4k, l) were indexed to lattice planes of Bragg’s reflection: diffraction peaks of (111), (200), (220), and (311) planes suggested that DH-AgNps and DH-AuNps were face-centered cubic and primarily composed of (111) orientation [4, 24]. The assigned peaks denoted by * at 27.89°, 32.33°, and 46.33° (2θ) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In order to determine the crystalline nature of the synthesized Ag nanochains, the synthesized nanochains were subjected to XRD analysis (Figure C) that clearly indicates the diffraction peaks at 2θ values of 32.29°, 38.04°, 44.69°, 46.42°, 53.49° and 57.1° corresponding to (122), (111), (200), (231), (142) and (241) planes of pure silver with face centered cubic structure JCPDS card no. 04‐0783 .…”
Section: Resultsmentioning
confidence: 99%